A colony-level response to disease control in a leaf-cutting ant - BROWN, MARK (Springer Verlag, 2002)
Parasites and pathogens often impose significant costs on their hosts. This is particularly true for social organisms, where the genetic structure of groups and the accumulation of contaminated waste facilitate disease transmission. In response, hosts have evolved many mechanisms of defence against parasites. Here we present evidence that Atta colombica, a leaf-cutting ant, may combat Escovopsis, a dangerous parasite of Atta?s garden fungus, through a colony-level behavioural response. In Atta colombica, garden waste is removed from within the colony and transported to the midden ? an external waste dump - where it is processed by a group of midden workers. We found that colonies infected with Escovopsis have elevated numbers of workers on the midden, where Escovopsis is deposited. Further, midden workers are highly effective in dispersing newly deposited waste away from the dumping site. Thus, the colony-level task allocation strategies of the Atta superorganism may change in response to the threat of disease to a third, essential party.
PUBLISHED
Keywords: Zoology